The Hypomnemata of Hegesippus - Eurell, John-Christian (Scottish journal of theology, 2022)
This article deals with the lost work of the early Christian writer Hegesippus, whose Hypomnemata is only known through quotations in Eusebius. Faulty preconceptions regarding the dating and provenance of Hegesippus’ work are criticised, and it is argued that the Hypomnemata is a loose collection of bishop traditions from the late 170s or 180s. The purpose of the work is to connect orthodoxy with correct episcopal succession.